The Effect of Working Capital Management and Family Ownership on Profitability and Liquidity (Study of Family Companies Listed on the Indonesia Stock Exchange in 2018-2022) - Rosidah Panjaitan; Herman Situmorang; Nida Abdilla Ritonga; Henny Setyo Lestari; Farah Margaretha Leon (International Journal Labs, 2023)
This article aims to examine the impact of working capital management and family ownership on the profitability and liquidity of family-owned companies listed on the Indonesia Stock Exchange from 2018 to 2022. The research utilizes a quantitative approach by analyzing financial data about working capital, family ownership, profitability, and company liquidity. The data used in the study is obtained from publicly available financial reports of family-owned companies listed on the Indonesia Stock Exchange. Data collection is conducted through a thorough review of documentation. The research sample consists of active family-owned companies that possess complete data for analysis. Multiple linear regression is employed to assess the relationship between working capital management, family ownership, profitability, and company liquidity. The findings reveal that both working capital management and family ownership significantly influence the profitability and liquidity of family firms. These findings offer valuable insights for family firm management to enhance their financial performance. Effective management of working capital can contribute to improved profitability and liquidity, while family ownership also plays a crucial role in determining the financial performance of family-owned companies. Furthermore, in addition to its practical implications, this research contributes theoretically to the existing literature on working capital management and family ownership, specifically in the context of family-owned companies in Indonesia.